2012
DOI: 10.1177/0892705712439568
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of coir fiber-reinforced ethylene glycol dimethacrylate-based composite

Abstract: The mechanical properties of the coir fibers were evaluated in this study. Tensile strength (TS), Young's modulus (YM) and elongation at break (Eb%) of virgin coir fibers were found to be 152 MPa, 5.3 GPa and 36%, respectively. Coir fibers were treated with ultraviolet (UV) radiation and were found to improve the mechanical properties significantly. Coir fiber-reinforced ethylene glycol dimethacrylate (EGDMA)-based composite was prepared and characterized. The surface of the coir fibers was modified with monom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…The presence of EDMA in the conductive film improved the interfacial adhesion between PVC/PEO blends and PAni. Roy et al 6 also found a similar trend in their research. The addition of ethylene glycol dimethacrylate showed further increase of tensile strength in the coir fibre-reinforced ethylene glycol dimethacrylate (EGDMA)-based composite.…”
Section: Tensile Propertiessupporting
confidence: 68%
“…The presence of EDMA in the conductive film improved the interfacial adhesion between PVC/PEO blends and PAni. Roy et al 6 also found a similar trend in their research. The addition of ethylene glycol dimethacrylate showed further increase of tensile strength in the coir fibre-reinforced ethylene glycol dimethacrylate (EGDMA)-based composite.…”
Section: Tensile Propertiessupporting
confidence: 68%
“…The content has shown remarkable results in the latest literature of the similar preparation method. 16,17,23 25 The final curing step was done by raising the temperature of the oven to 150°C and the end of the curing was confirmed using differential scanning calorimetry (DSC). Like in the study of Ahmad et al, 3 no residual exothermic process was observed in the DSC curve.…”
Section: Methodsmentioning
confidence: 99%
“…It is understandable that the integration of EDMA in the conductive composite films upgraded the filler-matrix interfacial adhesion as agreed by Roy et al who found a similar trend in their research. 10 The addition of ethylene glycol dimethacrylate showed further increase of tensile strength in the coir fibre-reinforced ethylene glycol dimethacrylate (EGDMA)-based composite.…”
Section: Tensile Propertiesmentioning
confidence: 99%